Beyond Tokenism: Indigenous Peoples’ Participation in Decision-Making in Community and National Park Governance in Nepal - Sherpa, Pasang; Chepang, Biswas (Journal of Nepalese Studies, 2025)
Indigenous Peoples living in and around national parks and conservation areas continue to face persistent challenges, including human-wildlife conflict, crop and shelter damage, restricted access to natural resources, bureaucratic obstacles in accessing compensation and inadequate institutional support. Addressing these issues requires not only more streamlined relief processes but also the meaningful participation of Indigenous Peoples communities in decision-making and culturally appropriate grievance redressal mechanism. Against this backdrop, employing Indigenous peoples and the capability approach and Arnstein’s Ladder of Participation as an analytical framework, this paper critically examines the extent and nature of Indigenous Peoples participation in the governance of community and national parks and Tharu peoples’ lived experiences of exclusion and inequality in the decision-making processes in Nepal. The study finds that many initiatives labelled as inclusive and participatory are largely tokenistic, failing to provide genuine community empowerment for their meaningful participation in decision making. This tokenism reinforces structural inequalities, limits Indigenous agency, and prevents communities from influencing decisions that directly affect their lands and livelihoods. This lack of meaningful participation perpetuates difficulties in securing compensation, maintains inefficient procedures, restricts access to resources, and ultimately reinforces the marginalization of Indigenous Peoples. The study findings reveal that without a shift from symbolic involvement to substantive authority and partnership, current governance frameworks risk perpetuating the marginalization they claim to address.